TRANSISI HUKUM PIDANA DAN KEDUDUKAN HUKUM ADAT DALAM HUKUM PIDANA BARU INDONESIA - Uti Abdulloh (INTELIGENSIA MEDIA, 2026)
The reform of Indonesian criminal law through Law Number 1 of 2023 on the National Penal Code marks a new chapter in the transition of Indonesian criminal law from the colonial Wetboek van Strafrecht to a criminal law rooted in national values. One of the most fundamental changes in the National Penal Code is the recognition of living law as regulated in Article 2 and Article 597, which opens space for customary law to serve as a basis for criminal liability alongside written law. This article aims to analyze the transition of Indonesian criminal law and the position of customary law following the enactment of the National Penal Code. This research employs a normative juridical method with statute and conceptual approaches. The findings indicate that the recognition of living law represents a paradigm shift from formal legality toward a balance with material legality, although its implementation requires clear guidelines to avoid legal uncertainty and potential human rights violations.